PENDAMPINGAN SERTIFIKASI HALAL PADA CAFE TAICHAN GORENG MAS MOY DI SALATIGA: PENDAMPINGAN SERTIFIKASI HALAL PADA CAFE TAICHAN GORENG MAS MOY DI SALATIGA - Wijayanto, Edi; Adhi, Nurseto; Rois, Muhammad; Martia, Dina Yeni; Listyani, Theresia Tyas; Widiyati, Sri; Rikawati (Politeknik Negeri Semarang, 2025)
The need for a halal lifestyle has become a necessity for the world community, especially Muslims. Indonesia as a country with the largest number of Muslims has its own potential and challenges in facing the development of the world's halal industry. In 2023, The Royal Islamic Strategic Studies Center (RISSC) noted that the Muslim population in Indonesia will reach 240.62 million people. This shows that Indonesia is a country with a Muslim majority. Halal certification is a guarantee of a product that has been declared permissible for consumption according to Islamic law. The Halal Certificate is issued by the Halal Product Guarantee Organizing Agency (BPJPH) which was formed in October 2017 based on the mandate of Law Number 33 of 2014 concerning Halal Product Guarantee (JPH) which was ratified on October 17, 2014. The implementation of Halal certification in Indonesia is mandatory for all food and beverage products with a deadline for implementing the obligation to be Halal certified on October 17, 2024. This community service program aims to assist in halal certification at the Cafe Taichan Goreng Mas Moy in Tegalrejo Salatiga. The methods used in this mentoring activity are through preparation, survey, mentoring through education and direction. The results of this mentoring activity are the existence of halal-certified products for Cafe Taichan Goreng Mas Moy Tegalrejo Salatiga, so that it can realize the government program regarding halal certification regulations.